Elevated CO2 causes different growth stimulation, water- and nitrogen-use efficiencies, and leaf ultrastructure responses in two conifer species under intra- and interspecific competition. (22nd April 2021) - Yu, Lei; Dong, Haojie; Huang, Zongdi; Korpelainen, Helena; Li, Chunyang
Abstract: The continuously increasing atmospheric carbon dioxide concentration ([CO2 ]) has substantial effects on plant growth, and on the composition and structure of forests. However, how plants respond to elevated [CO2 ] (e[CO2 ]) under intra- and interspecific competition has been largely overlooked. In this study, we employed Abies faxoniana Rehder & Wilson and Picea purpurea Mast. seedlings to explore the effects of e[CO2 ] (700 p.p.m.) and plant–plant competition on plant growth, physiological and morphological traits, and leaf ultrastructure. We found that e[CO2 ] stimulated plant growth, photosynthesis and nonstructural carbohydrates (NSC), affected morphological traits and leaf ultrastructure, and enhanced water- and nitrogen (N)- use efficiencies in A. faxoniana and P. purpurea . Under interspecific competition and e[CO2 ], P. purpurea showed a higher biomass accumulation, photosynthetic capacity and rate of ectomycorrhizal infection, and higher water- and N-use efficiencies compared with A. faxoniana . However, under intraspecific competition and e[CO2 ], the two conifers showed no differences in biomass accumulation, photosynthetic capacity, and water- and N-use efficiencies. In addition, under interspecific competition and e[CO2 ], A. faxoniana exhibited higher NSC levels in leaves as well as more frequent and greater starch granules, which may indicate carbohydrate limitation. Consequently, we concluded that under interspecific competition, P. purpurea possesses a positive growth and adjustment strategy (e.g. a higher photosynthetic capacity and rate of ectomycorrhizal infection, and higher water- and N-use efficiencies), while A. faxoniana likely suffers from carbohydrate limitation to cope with rising [CO2 ]. Our study highlights that plant–plant competition should be taken into consideration when assessing the impact of rising [CO2 ] on the plant growth and physiological performance.